Pengaruh Citra Merek dan Persepsi Harga Terhadap Keputusan Pembelian Konsumen Produk Kopi FamilyMart di Jakarta Timur: The Influence of Brand Image and Price Perception on Consumer Purchasing Decisions of FamilyMart Coffee Products in East Jakarta - Muhammad Zainal Muttaqim; Ulta Rastryana; Rini Larasati Irawan (CV Warnak Johanna Nusantara, 2026)
The rapid growth of Indonesia's coffee industry has driven the emergence of convenience stores such as FamilyMart, which offer ready-to-drink coffee through its FamiCafe concept, where consumer purchase decisions are still influenced by various factors, including brand image and price perception. This study aims to determine the influence of Brand Image and Price Perception on the Purchase Decisions of FamilyMart coffee product consumers in East Jakarta, both partially and simultaneously. A quantitative associative-causal method was applied using purposive sampling on 100 respondents determined through the Cochran formula. Data were collected through a Likert-scale questionnaire and analyzed using validity, reliability, classical assumption tests, t-test, F-test, the coefficient of determination, and multiple linear regression with SPSS version 27. The results show Brand Image has a positive and significant partial effect on Purchase Decisions (t-value 6.992 > t-table 1.984; sig. 0.000), as does Price Perception (t-value 2.555 > t-table 1.984; sig. 0.012). Simultaneously, both variables have a positive and significant effect (F-value 61.864 > F-table 3.090; sig. 0.000) with a coefficient of determination of 56.1% (R² = 0.561) and a regression equation of Y = 12.347 + 0.636X1 + 0.220X2.